The Level of Information Security Awareness among Academic Staff in IHL - Othman, Mohd Fairuz Iskandar; Alqahtani, Fayez; Bari, Md Ahsanul; Che Pee, Ahmad Naim; Abdul Rahim, Yahaya; Sulaiman, Hamzah Asyrani (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
IS security awareness plays a significant role in the process of the overall information security of any organisation. Based on an empirical study of 368 academic staff in three institutions of higher learning (IHL), we found that the level of information security awareness can be considered good, but it can certainly be improved further. Employees need further training in this area mainly at institutions which only recently received the ISO/IEC 27001:2013 certification. Our sample seems to suggest that demographics such as the age of the respondents contributed to their information security risk tolerance and adherence behaviour.